Archaeologies of the British in Latin America - Orser Jr., Charles E.; SpringerLink (Online service) (Cham : Springer International Publishing : Imprint: Springer, 2019)
This volume includes chapters by historical archaeologists engaged in original research examining the role of the British Empire in Latin America. The archaeology of Latin America is today a rapidly expanding field, with new research being accomplished every day. Currently, the vast amount of research is being focused on the Spanish Empire and its agents' interactions with the region's indigenous peoples. Spain, however, was not the only international power intent on colonizing and controlling Latin America. The British Empire had a smaller albeit significant role in the cultural history of Latin America. This history constitutes an important piece of the historical story of Latin America. Archaeologies of the British in Latin America presents the results of original research and begins a dialogue about the archaeology of the British Empire in Latin America by an international group of archaeological scholars. Fresh insights on the complex history of cultural interaction in one of the world's most important regions are included. It will be of interest to historical archaeologists, Mesoamerican archaeologists engaged in pre-contact research, Latin American and global historians, Latin American anthropologists, material culture specialists, cultural geographers, and others interested in the cultural history of colonialism in general and in Latin America in particular.
Archaeological Research and the British in Latin America -- Kaxil Uinic: Archaeology at a San Pedro Maya Village in Belize -- Portrait of a Port: The Objects of Industry in Nineteenth-Century Acajutla, El Salvador (1805-1900) -- The Nineteenth-Century British Ceramics Trade to Southwestern South America: An Initial Characterization of the Archaeological Evidence from Chile -- Re-centering the Narrative: British Colonial Memory and the San Pedro Maya -- An English House in Alexandra Colony, Santa Fe, Argentina, 1870-85 -- From the Canopy to the Caye: Two of Britain's Colonial Ventures in Nineteenth-Century Belize -- You Don't Have to Live Like a Refugee: Consumer Culture at the Nineteenth-Century Refugee Village at Tikal, Guatemala -- Landscape of Royalization: A British Military Outpost on Roatán Island, Honduras -- Railways: Landmarks and Scars in the Atlantic Rainforest -- Archaeology of the Industrial Revolution and Building Construction Systems: Edward Taylor and his Failed Project in Argentina, 1852 -- Social and Environmental Impacts of British Colonial Rum Production at Betty's Hope Plantation, Antigua -- The British in Latin America: Material Evidence of Empire and Beyond.
Keywords: Archaeology; Archaeology